Pursuit Curves and Ordinary Differential Equations - Zuzana Malacka (Communications - Scientific letters of the University of Zilina, 2012)
This paper deals with the differential equations which describe curves of pursuit, in which the pursuer’s velocity vector always points directly towards the pursued. We use the Laplace Transform method to solve the classic problem of four mice pursuit.